More Human BM-MSC With Similar Subpopulation Composition and Functional Characteristics Can Be Produced With a GMP-Compatible Fabric Filter System Compared to Density Gradient Technique - Spohn, Gabriele; Witte, Anne-Sophie; Kretschmer, Anja; Seifried, Erhard; Schäfer, Richard (Frontiers in Cell and Developmental Biology, 2021)
Background: Mesenchymal Stromal Cells (MSC), multipotent progenitors that can be isolated from a variety of different tissues, are becoming increasingly important as cell therapeutics targeting immunopathologies and tissue regeneration. Current protocols for MSC isolation from bone marrow (BM) rely on density gradient centrifugation (DGC), and the production of sufficient MSC doses is a critical factor for conducting clinical MSC trials. Previously, a GMP-compatible non-woven fabric filter device system to isolate MSC was developed to increase the MSC yield from the BM. The aim of our study was to compare high resolution phenotypic and functional characteristics of BM-MSC isolated with this device and with standard DGC technology. Materials and Methods: Human BM samples from 5 donors were analyzed. Each sample was divided equally, processing by DGC and with the filter device. Stem cell content was assessed by quantification of colony forming units fibroblasts (CFU-F). Immunophenotype was analyzed by multicolor flow cytometry. In vitro tri-lineage differentiation potential, trophic factors and IDO-1 production were assessed. Functionally, immunomodulatory potential, wound-healing and angiogenesis were assayed in vitro. Results: The CFU-F yield was 15-fold higher in the MSC preparations isolated with the device compared to those isolated by DGC. Consequently, the MSC yield that could be manufactured at passage 3 per mL collected BM was more than 10-times higher in the device group compared to DGC (1.65x109 vs. 1.45x108). The immunomodulatory potential and IDO-1 production showed donor-to-donor variabilities without differences between fabric filter-isolated and DGC-isolated MSC. The results from the wound closure assays, the tube formation assays and the tri-lineage differentiation assays were similar between the groups with respect to the isolation method. Sixty-four MSC subpopulations could be quantified with CD140a+CD119+CD146+ as most common phenotype group, and CD140a+CD119+CD146+MSCA-1-CD106-CD271- and CD140a+CD119+CD146-MSCA-1-CD106-CD271-as most frequent MSC subpopulations. As trophic factors HGF, EGF, BDNF, Angiopoietin-1 and VEGF-A could be detected in both groups with considerable variability between donors, but independent of the respective MSC isolation technique. Conclusions: The isolation of MSC using a GMP-compatible fabric filter system device resulted in higher yield of CFU-F, producing substantially more MSC with similar subpopulation composition and functional characteristics as MSC isolated by DGC.